SOCIAL MEDIA AS A BUSINESS TOOL: A BIBLIOMETRIC REVIEW ON BRAND BUILDING AND CUSTOMER ENGAGEMENT - Sudie, Ernamurni; Saaidun, Noor Saidatul Natrah; Syed Radzuan, Syarifah Fairuz (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The increasing integration of social media into business strategies has transformed how firms build brands and engage customers, prompting a surge in academic interest across multiple disciplines. Despite this growing body of literature, there remains a need for a structured overview of research trends, key contributors, and thematic developments in this area. This study conducts a comprehensive bibliometric analysis to explore the research landscape on social media as a business tool: building brands and engaging customers. Using the Scopus database, a refined search strategy was applied with the keywords social media, business, and firm, limited to English-language journal articles published between 2007 and 2023. After applying inclusion and exclusion criteria, a total of 643 relevant journal article were identified for analysis. To examine the dataset, a combination of bibliometric tools which are Scopus Analyzer, OpenRefine, and VOSviewer was utilized to extract and visualize data on publication trends, influential articles, author collaboration networks, country productivity, and keyword co-occurrence. The results reveal that the United States leads in publication output, while high impact articles focus on firm-generated content, customer engagement, and business transformation. Popular keywords such as social media marketing, entrepreneurship, firm performance, and customer behavior indicate key research directions. VOSviewer’s mapping further highlights emerging themes like sustainability, innovation, and digital transformation. The study also uncovers notable international collaborations, with strong research linkages between developed and emerging economies. These findings provide valuable insights into the intellectual structure and evolution of the field, offering guidance for future research directions and highlighting the strategic role of social media in business performance.